Perspective on Adversity in Toxicology Evaluations. (February 2021) - Engelhardt, Jeffery A.; Dorato, Michael A.
Determining adversity of effects in toxicology studies continues to pose a dilemma to practicing toxicologists and pathologists. How this determination is made may follow either a focused or broad approach to assessing the study data. The choice of which approach is best is dependent on a variety of factors. Therefore, we present a philosophical perspective on the determination of adversity across toxicology studies that may be applied in inhalation studies and those conducted by other routes of exposure.